THE ROLE OF AUDIO-VISUAL AIDS IN IMPROVING UNDERSTANDING OF GRAMMAR CONCEPTS FOR 6THE-GRADE STDENTS (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Grammar instruction in middle school English classrooms often relies on explanations and repetitive exercises, which can limit understanding. This study examines how structured audio-visual instruction affects grammar learning for sixth-grade students. Lessons included animated presentations, videos, visual sentence mapping, and guided listening activities. Data were collected through tests, classroom observations, and student reflections. The results show that using audio-visual materials improves grammar understanding, increases engagement, and helps students use grammar in context. Low-cost multimedia strategies can support effective grammar teaching in middle schools.